Interaksi Antara Nilai Cashback, Ketentuan Cashback, dan Platform E-Commerce Terhadap Minat Beli Konsumen : (Studi Kasus Pada Pengguna Shopee Di Kota Sidoarjo) - Deny Ardiansyah; Afifatus Sholichah; Andini Fitria Rahmadani; Mochammad Nafis; Lintang Cahya Kusuma; Thalita Al Faustina (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
The development of technology and the internet has brought changes in the way consumers purchase goods and services. E-commerce platforms such as Shopee have become one of the popular platforms for consumers to shop online (Sudiantini et al., 2023). This research aims to examine the influence of cashback value, cashback conditions, and e-commerce platforms on consumer purchasing interest, with a focus on Shopee users in Malang City. A case study conducted on Shopee users in Malang City was chosen as the focus of the research because of the rapid growth of users of this platform and there is still little research conducted on the Shopee e-commerce platform specifically. The research results show that the cashback value does not have a significant influence on consumer buying interest, as evidenced by the P.Values ​​value of 0.828 and T-statistics of 0.217, which do not meet the significance criteria (P.Values ​​< 0.05 and T -statistics > 1.96). The method in this research uses quantitative research, which consists of the cashback value variable, cashback provisions and e-commerce platform which are independent variables and consumer buying interest is the dependent variable. Data collection techniques are techniques used by researchers to obtain data in a study (Stevanus & Pratiwi, 2019)